Importance of proper patient selection and endpoint selection in evaluation of new therapies in acute stroke: further analysis of the SENTIS trial. (3rd January 2013) - Shuaib, Ashfaq; Schwab, Stefan; Rutledge, J Neal; Starkman, Sidney; Liebeskind, David S; Bernardini, Gary L; Boulos, Alan; Abou-Chebl, Alex; Huang, David Y; Vanhooren, Geert; Cruz-Flores, Salvador; Klucznik, Richard Paul; et al.
Abstract : Background: The magnitude of treatment effect in acute stroke depends on several factors, including time from symptom onset (TFSO) to treatment and severity of the initial insult. Objective: To report further evaluation of NeuroFlo therapy, focusing on the effect of time and stroke severity. Methods: SENTIS was a prospective randomized trial (N=515) comparing standard medical therapy with/without NeuroFlo therapy. For this analysis, we evaluated outcomes in groups of patients based on TFSO and stroke severity: patients randomized <6 h, 6–10 h, and >10 h with mild (NIHSS<8), moderate (8–14), and severe (>14) symptoms at randomization. 90-Day mRS (modified Rankin Scale) scores and stroke-related death rates were compared between treatment groups. Results: For patients randomized <6 h TFSO (n=128), the OR for mRS 0–2 was 3.11 (CI 1.30 to 7.46, p=0.011) for treated versus non-treated patients. In patients with disease of moderate severity (NIHSS 8–14, n=214), NeuroFlo-treated patients were more likely to have a good outcome (mRS 0–2; OR=1.84, CI 1.02 to 3.33, p=0.043). The stroke-related death rate was better in the treated group with TFSO >10 h and NIHSS >14 (n=42) (OR=7.10, CI 1.13 to 44.55, p=0.036). Conclusions: The results of our analysis support the importance of careful selection of outcome measures and the impact that rapid treatment and initial stroke severity have on outcome. Clinical trial registration URL://http.clinicaltrials.gov .Unique identifier: NCT00119717 .